Peritoneal Dialysis-Related Peritonitis due to Melioidosis: A Potentially Devastating Condition. Issue 2 (March 2017) - Kanjanabuch, Talerngsak; Lumlertgul, Nuttha; Pearson, Lachlan J.; Chatsuwan, Tanittha; Pongpirul, Krit; Leelahavanichkul, Asada; Thongbor, Nisa; Nuntawong, Gunticha; Praderm, Laksamon; Wechagama, Pantiwa; Narenpitak, Surapong; Wechpradit, Apinya; et al.
Background: Melioidosis, an infectious disease caused by Burkholderia pseudomallei, is endemic in Southeast Asia and Northern Australia. Although a wide range of clinical manifestations from this organism are known, peritonitis associated with peritoneal dialysis (PD) has rarely been reported. Patients and Methods: Peritoneal dialysis patients from all regions in Thailand were eligible for the study if they had peritonitis and either peritoneal fluid or effluent culture positive for B. pseudomallei . Patient data obtained included baseline characteristics, laboratory investigations, treatments, and clinical outcomes. When possible, PD fluid and removed Tenckhoff (TK) catheters were submitted for analyses of minimal inhibitory concentration (MIC) and microbial biofilm, respectively. Results: Twenty-six patients were identified who were positive for peritoneal B. pseudomallei infection. The recorded mean age was 50 ± 15 (24 – 75) years, and the majority (58%) were female. Most of the cases were farmers living in Northeastern and Northern Thailand. Almost half of the cases had diabetes. Infections were reported commonly during the monsoon season and winter. The clinical presentations of peritonitis were similar to the manifestations from other microorganisms. Nine patients (41%) died (7 from sepsis), 6 fully recovered, and 7 switched to permanent hemodialysis. The mortality was potentially associated with sepsis ( p = 0.007), infection during the monsoon season ( p = 0.017), high initial dialysate neutrophils ( p = 0.045), and high hematocrit ( p = 0.045). Although no antibiotic resistance to ceftazidime and carbapenems was detected, approximately 50% of patients died with this treatment. Microbial biofilms were identified on the luminal surface of 4 out of 5 TK catheters, but the removal of the catheter did not alter the outcomes. Conclusion: Peritoneal dialysis-related peritonitis due to melioidosis is uncommon but highly fatal. Increased awareness, early diagnosis, and optimal management are mandatory.